1992
DOI: 10.1029/92tc00636
|View full text |Cite
|
Sign up to set email alerts
|

A major Late Devonian‐Early Carboniferous (Hercynian) Thermotectonic event at the NW Margin of the Arabian‐Nubian Shield: Evidence from zircon fission track dating

Abstract: Zircon fission track (ZFT) ages of 17 Precambrian samples from deep boreholes and outcrops in southern Israel and Sinai fall within the range 328–373 Ma (Late Devonian‐Early Carboniferous). Single zircon grain age distributions are unimodal with a high chi‐square probability. The age data indicate total resetting of the ZFT clocks but only partial resetting of coexisting sphenes, constraining the temperatures attained to about 225° ± 50°C, followed by relatively rapid regional cooling at the times indicated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
7
37
0
Order By: Relevance
“…These conclusions agree with an earlier ZFT study from boreholes in Sinai and southern Israel (Kohn et al, 1992) and basement rocks in the Eastern Desert of Egypt (Bojar et al, 2002). ZFT ages for the Precambrian basement and infra-Cambrian sediments in the subsurface of Israel (Zenifi m Formation) are within the range 328-373 Ma, consistent with our results for the Shehoret Formation.…”
Section: Post-depositional Thermal and Burial Historysupporting
confidence: 93%
See 1 more Smart Citation
“…These conclusions agree with an earlier ZFT study from boreholes in Sinai and southern Israel (Kohn et al, 1992) and basement rocks in the Eastern Desert of Egypt (Bojar et al, 2002). ZFT ages for the Precambrian basement and infra-Cambrian sediments in the subsurface of Israel (Zenifi m Formation) are within the range 328-373 Ma, consistent with our results for the Shehoret Formation.…”
Section: Post-depositional Thermal and Burial Historysupporting
confidence: 93%
“…ZFT ages for the Precambrian basement and infra-Cambrian sediments in the subsurface of Israel (Zenifi m Formation) are within the range 328-373 Ma, consistent with our results for the Shehoret Formation. Although the lower Paleozoic of southern Israel is less than 300 m thick, Kohn et al (1992) inferred that the basement must have been covered by a thick sedimentary cover that was rapidly removed during an important late Devonian-early Carboniferous tectonic event. This inference was based on their thermochronometric data and the same regional stratigraphic considerations summarized in the previous paragraph.…”
Section: Post-depositional Thermal and Burial Historymentioning
confidence: 98%
“…Interestingly, after first findings of Kohn et al (1992), increasing lines of evidence converge to show the existence of Late Paleozoic geological events (from 420 Ma to 310 Ma) not only in Central Iran (Bagheri and Stampfli, 2008;Zanchi et al, 2009a and b;Buchs et al, 2013;Moghadam et al, 2015) but also in the northern part of the Arabian plate Tavakoli-Shirazi et al, 2013;Stern et al, 2014) to which SSMZ was likely related.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Furthermore, Kohn et al (1992) found a Late DevonianEarly Carboniferous thermo-mechanical event that they related to the "Variscan" orogeny, which is also known in the study area (Shakerardakani et al, submitted). A so-called "Hercynian unconformity" exists everywhere in the Arabian plate (Frizon de Lamotte et al 2013 and references therein).…”
Section: Discussionmentioning
confidence: 99%